Non-obvious effects of montelukast – leukotriene receptor blocker: frigoprotective and anticonvulsant properties - S.Yu. Shtrygol; I.G. Kapelka; M.V. Mishchenko; O.Ya. Mishchenko (Medičnì Perspektivi, 2021)
The participation of arachidonic acid metabolism products – prostaglandins and leukotrienes – in the process of inflammation is a common pathogenetic link of cold injury and epilepsy. Montelukast is widely used for the treatment of bronchial asthma and allergic rhinitis as a leukotriene receptor blocker. However, the mechanism of action of the drug suggests a wider range of its pharmacological properties and the corresponding scope of application. This study is aimed to determine the effectiveness of montelukast as a potential frigoprotective and anticonvulsant drug. Experiments were performed on 73 white mice weighing 20-22 g on models of acute general cooling and pentylenetetrazol convulsions. Frigoprotective properties were studied at a temperature of –18°C, recording the lifetime. Montelukast ("Singular", 2 mg/kg), acetylsalicylic acid ("Aspirin", 50 mg/kg), celecoxib ("Celebrex", 74 mg/kg), diclofenac sodium ("Voltaren", 14 mg/kg) were administered intragastrically as a suspension in a prophylactic mode, 30 minutes before the cold injury. In the study of anticonvulsant activity, montelukast ("Singular", 4 mg/kg) and sodium valproate ("Depakin", 300 mg/kg) were administered intragastrically 30 minutes before stimulating convulsions by subcutaneous administration of pentylenetetrazole (90 mg/kg). The latent period of convulsions, the number of convulsions per 1 animal, % of mice with clonic and tonic paroxysms, the severity of convulsions in points, the duration of the convulsive period, the lifetime of animals and lethality were recorded for an hour. On the model of acute general cooling, montelukast showed a dose-dependent frigoprotective effect at a dose of 2 mg/kg surpassing drugs with proven frigoprotective properties – acetylsalicylic acid and celecoxib. On the model of pentylenetetrazole-induced convulsions, montelukast statistically significantly reduced the integral indicator of anticonvulsant activity – lethality – by 2.57 times. Thus, the experiment proved the significant role of leukotrienes in the pathogenesis of cold injury and epilepsy and justified the feasibility of further study of the frigoprotective and anticonvulsant properties of montelukast – leukotriene receptor blocker a drug as for adjuvant therapy, especially when these pathologies are combined with bronchial asthma and allergic rhinitis.